Role of Radiation Processing in Production of Hydrogels For Medical Applications - D. Darwis (PPIKSN-BATAN, 2009)
Recently, hydrophilic polymer gel (hydrogel) for application in medical fields has attracted much attention of researchers due to its unique properties which can resemble human living organs. Wound dressing, contact lenses and drug delivery system are among their applications in medical field. High energy radiation especially gamma ray and electron beam is often used for synthesis and modification of hydrogel. Through radiation crosslinking and or grafting process, hydrogel with specialty properties for specific application can be made. The advantage of radiation synthesized hydrogel over conventional methods is very pure products are obtained since the present of chemical initiators are not required; The preparation of sample does not require special sterile production rooms but still enables to obtain a sterile product; The irradiation process is easily controlled; Synthetis of new polymers and bulk or surface modification of commercial products can be accomplished with additional advantage of possibility of a concurrent sterilization. The future prospect of hydrogel seems to be in tissue engineering and diagnostic fields. Received: 27 February 2009; Reevised: 27 May 2009; Accepted: 16 June 2009